Utilization of Cow Milk Enriched with Conjugated Linoleic Acid to Decrease Body Weight, Cholesterol, Low Density Lipoprotein and to Increase Blood High Density Lipoprotein - Suhartati, FM; Suryapratama, W; Rahayu, S (ANIMAL PRODUCTION, 2012)
An experiment to investigate the ability of cow milk enriched with conjugated linoleic acid to decrease body weight, total cholesterol, blood Low Density Lipoprotein (LDL), and to increase blood High Density Lipoprotein (HDL) has been conducted using in vivo experimental method. Research material consisted of 40 8-week-old white female rats (Rattus norvegicus) of Wistar strain (as an animal model). The method used was an experimental method with a Completely Randomized Design. The treatments tested were P1 = high-fat ration containing 27.66% fat (HF), P2 = HF + 5 ml of milk/head/day, P3 = HF + 10 ml of milk/head/day, P4 = low-fat ration containing 5% fat (LF). Each treatment was repeated five times to make 20 experiment units, each consisted of two rats. Body weight gain, total cholesterol, LDL-cholesterol and HDL-cholesterol were observed. The data obtained were then analyzed using analysis of variance followed by orthogonal contrast test. Orthogonal polynomials tests was applied to evaluate the response variables. The results showed that 10 ml/head/day of cow milk was needed to decrease body weight of hypercholesterolemic rats and 5 ml/head/day of cow milk was needed to decrease total cholesterol, LDL-cholesterol and to increase blood HDL-cholesterol of hypercholesterolemic rats.Keywords: cow milk, conjugated linoleic acid, body weight gain, cholesterol.Â Animal Production 14(2):70-76